2020
DOI: 10.1021/acschemneuro.0c00739
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of N-Cyclohexylethyl-[A/G]-[D/E]-X-V Peptides on Ischemic Stroke by Blocking nNOS–CAPON Interaction

Abstract: The protein−protein interaction between neuronal nitric oxide syntheses (nNOS) and the carboxy-terminal PDZ ligand of nNOS (CAPON) is a potential target for the treatment of ischemic stroke. Our previous study had identified ZLc-002 as a promising lead compound for inhibiting nNOS−CAPON coupling. To find better neuroprotective agents disrupting the ischemia-induced nNOS−CAPON interaction, a series of N-cyclohexylethyl-[A/G]-[D/E]-X-V peptides based on the carboxy-terminal tetrapeptide of CAPON was designed, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…To further examine the role of SERT-nNOS coupling in the DRN as it relates to depression, we screened our compound library previously established on the basis of nNOS-mediated protein-protein interactions, some of which has been published previously ( 23 26 ). Unexpectedly, we found that two compounds of the Sakura series (fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further examine the role of SERT-nNOS coupling in the DRN as it relates to depression, we screened our compound library previously established on the basis of nNOS-mediated protein-protein interactions, some of which has been published previously ( 23 26 ). Unexpectedly, we found that two compounds of the Sakura series (fig.…”
Section: Resultsmentioning
confidence: 99%
“…2e). Increased mRNA levels of the Wnt target genes Axin2, LEF1, and Bmp2 (Riese et al, 1997;Jho et al, 2002;Lewis et al, 2010) were induced by Wnt3a treatment, as measured by qRT-PCR, and these increases were reduced by compounds 18, 20, and 21 (Fig. 2f).…”
Section: Comparison To Reported Dvl Pdz-binding Molecule Subsectionmentioning
confidence: 94%
“…Uncoupling nNOS-CAPON inhibits the excitotoxic activation of p38MAPK and subsequent neuronal death [ 119 ]. The nNOS-CAPON inhibitor N-cyclohexylethyl-AD(OMe)AV, designed by targeting the PDZ of nNOS, has a neuroprotective effect on ischemic stroke in rats [ 120 ]. Interestingly, it has been reported that the CAPON PDZ ligand motif does not bind to nNOS, and in contrast, full-length CAPON forms an unusually stable interaction with nNOS.…”
Section: Nnos-capon Interaction and Neurological Diseasesmentioning
confidence: 99%